SUSTAINABILITY REPORTING DISCLOSURE ANALYSIS AND PLATINUM RATING ASRRAT 2023 PT PETROKIMIA GRESIK REPORTING PERIOD 2022 - Darman, Darman Saputra; Wibawa, Dian Prihardini; Julia, Julia (Jurnal Mebis, 2024)
This study aims to reveal sustainability reporting that supports the fact that PT Petrokimia Gresik in 2022 became one of the platinum winners in the 2023 ASRRAT ranking. This type of research is a qualitative descriptive approach with the Content Analysis method in the 2022 PT Petrokimia Gresik sustainability report. The company PT Petrokimia Gresik has disclosed their sustainability performance 100% in accordance with the 2021 GRI standards, so this shows a strong commitment to transparency and accountability in various aspects of their operations, including economic, social, and environmental performance. Based on the results of the analysis with the analysis method used, the results of the fully applied test were obtained so that this confirms the fact that PT Petrokimia Gresik in 2022 received platinum in the 2023 ASRRAT rating. It is hoped that in the future the sustainability reporting period will continue to sharpen the level of full applied compliance and continue to strive to improve full applied compliance. and support the concept of sustainability that has a good impact on internal and external stakeholders.